The Effect of Household Health and Education Expenditures and Macroeconomic Conditions on Cigarette Consumption: A Panel Data Study of 34 Provinces in Indonesia, 2021–2023 - Rahmat Widianto Wibowo; Dini Hariyanti; Sumiyarti Sumiyarti (Dinasti Publisher, 2025)
This study aims to analyze the effects of household expenditures on health and education, as well as macroeconomic conditions, on cigarette consumption across 34 provinces in Indonesia during the 2021–2023 period. A quantitative approach is employed using a fixed-effects panel data model to systematically estimate the relationships among the variables. The novelty of this study lies in the integration of both micro-level variables (household expenditure on health and education) and macroeconomic indicators (GRDP growth, open unemployment rate, and poverty depth index) into a unified analytical framework using recent provincial panel data. This approach has rarely been adopted in previous studies, which predominantly relied on cross-sectional household-level data and tended to isolate micro or macro factors. The results indicate that household health expenditures, the poverty depth index, and the unemployment rate have a significant negative effect on cigarette consumption. In contrast, household education expenditures and GRDP growth do not exhibit statistically significant impacts. These findings suggest that increased spending on health may reduce cigarette consumption through a budget reallocation mechanism (crowding-out effect), whereas education-related spending shows no practical short-term influence. The study implies that public policy interventions should prioritize enhancing household investments in health while simultaneously addressing macroeconomic pressures that contribute to smoking behavior. It is recommended that future research extends the observation period, incorporates sociocultural variables, and includes behavioral dimensions to obtain a more comprehensive understanding of household cigarette consumption patterns across regions in Indonesia. These insights are expected to support the development of evidence-based public policies aligned with national health and education agendas.